Palace of the Emirate of Bukhara from the history of music and musical art (80-s of the XIX th century and the beginning of the XX th century) - Radjabova Nodira Mehmonovna; Abdurauf Fitrat (Genius Journals, 2022)
This article scientifically analyzes the emergence of the art of palace music at the last historical stage of the Bukhara Emirate, the fact that it went through several historical stages, the factors that influenced its formation and development. There is also information about the formation of a troupe of women musicians in the palace of the Bukhara Emirate, their national and social composition, names, skills, real names and nicknames of a number of musicians. Alimkhan's mother, who, like Eshan's mother, was the last emir, made a significant contribution to the formation of a group of palace musicians. The article also discusses the traditions of the teacher and student, the conditions for the transition from student to teacher, the skills of students in the performing arts of music. The main features of the songs of the "Bukhara" cycle are that they are sung in a playful way, there is a place for sweet speeches, and the transition from composure to cheerful songs speeds up the dance process. It is reported that only women played music in the palace and that they received financial incentives. This small study reveals the uniqueness of the art of dance, such as bells, bells, rusty belts.
Keywords: Bukhara; Bukhara dance; musician; bell